2022
DOI: 10.3889/oamjms.2022.7969
|View full text |Cite
|
Sign up to set email alerts
|

Length Attainment and Stunting Prevalence of Children aged 0–24 Months Living in the Area of Clay Brick Kilns in Pagar Merbau Sub District, Indonesia

Abstract: BACKGROUND: The association of air pollution with children’s health and growth has been proved. AIM: This study aimed to assess the length attainment and stunting prevalence of children living in the areas of clay brick kiln and non-clay brick kilns. METHODS: The study was a cross-sectional study conducted from February to December 2020. The location of the study was in Pagar Merbau Subdistrict, Deli Serdang District, North Sumatera Indonesia. Four villages were selected purposively to be the location of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Among children whose first episode of migration to a kiln occurred before age 6 months, the odds of stunting were 1.6 (95% CI 1.17 – 2.19) and 2.1 (1.30 – 3.41) times higher in those with two and three migration episodes, respectively, when compared to one. Sinaga et al 89 evaluated 192 children from Indonesia aged 0-24 months who lived in villages with (n=101) and without (n=91) clay brick kilns. The overall prevalence of stunting was 19%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among children whose first episode of migration to a kiln occurred before age 6 months, the odds of stunting were 1.6 (95% CI 1.17 – 2.19) and 2.1 (1.30 – 3.41) times higher in those with two and three migration episodes, respectively, when compared to one. Sinaga et al 89 evaluated 192 children from Indonesia aged 0-24 months who lived in villages with (n=101) and without (n=91) clay brick kilns. The overall prevalence of stunting was 19%.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined the role of brick kiln pollution on child linear growth (e.g., stunting). 7,85,90 Nasir et al 7 examined 383 children aged 5-12 years from Pakistan, measured their height and calculated Z-scores using the 2007 World Health Organization (WHO) international reference. Mean height-for-age Z-score was -0.50 (prevalence of stunting not reported).…”
Section: Linear Growthmentioning
confidence: 99%
“…However, this will be a challenge for the Indonesian government in reducing the prevalence of stunting from 30.7% to 14.0% in 2024. In addition, the number of newborns with birth length less than 48 cm increased from 20.2% to 22, 7% (Sinaga et al 2022) The current literature review study fills the current information gap by examining more of the health impacts of air pollution and stunting on children, for example infant mortality, low birth weight, and premature birth, and so on. Apart from that, to understand the many problems related to pollution.The impact of air pollution contributes to stunting, potentially in developing countries and recognized by WHO as a "health emergency" worldwide, air pollution can be severe, especially for children living in low-or middle-income countries, where air quality levels are far from exceeds WHO health-based guidelines (World Health Organisation (WHO) 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several studies have found that household air pollution, indoor solid fuels, and kitchen smoke exposure negatively impact children's health including anthropometric measurements. A study conducted by Bobak et al which revealed that the effect of air pollution on children's height begins at the age of 2 years and becomes apparent at the age of 7 years (Sinaga et al 2022). The impact of air pollution contributes to 3-9% of stunting prevalence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation